Order of transcription of genes of vesicular stomatitis virus. - Ball, L A (1976)
The effect of ultraviolet radiation on the expression of the genes of vesicular stomatitis virus (VSV) was studied in a cell-free system which executed coupled transcription and translation of the viral genes. In this system, which contained detergent-activated virus and a cytoplasmic extract of mouse L-cells, three of the five viral proteins (N, NS, and M) were synthesized accurately and efficiently; a putative precursor to the viral glycoprotein (G) was also made, but synthesis of the L protein was not detected. In response to irradiation of VSV, the synthesis of each protein in the coupled system displayed a characteristic single-hit inhibition. This permitted calculation of the apparent target-sizes for expression of the different viral genes relative to the entire genome (3.6 to 4.0 X 10(6) daltons) as measured by loss of infectivity. These are: N, 0.55 X 10(6); NS, 0.83 X 10(6); M, 1.12 X 10(6); G, 1.76 X 10(6) daltons of RNA. Only the N protein gene has a target-size which corresponds to that predicted from the molecular weight of its messenger RNA (molecular weight: 0.55 X 10(6)). The target-sizes for the other three genes are two to four times larger than expected, and are not proportional to the molecular weights of their corresponding messenger RNAs (molecular weights: NS, 0.28 X 10(6); M, 0.28 X 10(6); G, 0.7 X 10(6)). The polar effect of UV irradiation is inconsistent with independent transcription of each of the genes of VSV. Rather, the target-sizes appear to be cumulative, suggesting that trnascription initiates at a single point on VSV RNA and proceeds in the order 3'-N-NS-M-G-(L)-5'.